Type-I Cryoglobulinaemia Associated to Monoclonal Gammapathy of Undetermined Significance - Duarte, Juan Manuel; Ocampo, Paloma; Ramos, Silvia Graciela; Carballo, Orlando Gabriel; Barcia, Ricardo E; Arévalo, Cecilia Elena (Prague medical report, 2020)
Cryoglobulins are immunoglobulins that undergo reversible precipitation at cold temperatures. Monoclonal type-I cryoglobulinaemia is the least frequent and is associated to hematological diseases such as multiple myeloma, Waldenström's macroglobulinaemia, chronic lymphocytic leukaemia and lymphoma. We describe the case of a 60-year-old female patient, who suffered from burning pain in her feet for ten months before her admission. The patient presented intermittent distal cyanosis that progressed to digital ischaemia. She also reported paresthesia in her hands, difficulty in writing, and a 26-kg-weight loss. At the physical examination, it was identified livedo reticularis, palpable purpura, and painful ecchymotic lesions in her calves and feet. Moreover, peripheral pulses were palpable and symmetrical. It was observed an atrophy of the right first dorsal interosseous and both extensor digitorum brevis, as well as a distal bilateral apalesthesia and allodynia. Both Achilles reflexes were absent. Laboratory tests revealed anemia, high erythrosedimentation rate and C-reactive protein. Serum protein electrophoresis showed a monoclonal IgG-Kappa gammopathy. The results also evidenced the presence of Bence-Jones proteinuria. The bone marrow biopsy revealed less than 10% of plasma cells, and skin biopsy informed leukocytoclastic vasculitis. The patient was treated with high-dose intravenous steroids and cyclophosphamide. The treatment showed that the skin lesions had improved, pain disappeared and motor deficit stopped its progression.
Keywords: Cryoglobulinemia; Humans; Monoclonal gammopathy of undetermined significance; lidé středního věku; monoklonální gamapatie nejasného významu; Multiple Myeloma; Female; dospělí; IgA vaskulitida; IgA Vasculitis; lidé; kryoglobulinemie; mnohočetný myelom; Adult; Cryoglobulinaemia; ženské pohlaví; Middle Aged; Monoclonal Gammopathy of Undetermined Significance; Vasculitis, Leukocytoclastic, Cutaneous; kožní leukocytoklastická vaskulitida; Neuropathy; Vasculitis